Wage-Price Setting in New EU Member States - Goretti, Manuela (Washington, D.C. : International Monetary Fund, 2008)
This paper analyzes wage- and price-setting relations in new EU member countries. Panel estimates indicate a strong and significant relationship between real wages and labor productivity, as well as evidence of wage pass-through to inflation. Terms of trade shocks do not feed through to real wages. Country-specific wage developments, beyond differences in labor productivity growth, are mostly explained by real wage catch-up from different initial levels and different labor market conditions. Qualitative evidence also suggests that public sector wage demonstration effects and institutional factors may play a role in wage determination.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet